Rapid Stepping Up of Carvedilol in Stable Congestive Heart Failure Patients - Rawat, B (Nepalese Heart Journal, 2004)
The utility of Beta-blockers in Congestive Heart Failure (CHF) patients is well established. Yet they are grossly underused drugs. Elther they are not prescribed at all or used in a very low dose. Also, here is no clear evidence based consensus regarding its dose titration or need of admission.